Influence of Isothermal ω Transitional Phase-Assisted Phase Transition From β to α on Room-Temperature Mechanical Performance of a Meta-Stable β Titanium Alloy Ti−10Mo−6Zr−4Sn−3Nb (Ti-B12) for Medical Application - Cheng, Jun; Li, Jinshan; Yu, Sen; Du, Zhaoxin; Zhang, Xiaoyong; Zhang, Wen; Gai, Jinyang; Wang, Hongchuan; Song, Hongjie; Yu, Zhentao (Frontiers in Bioengineering and Biotechnology, 2021)
The microstructural evolution and tensile performance of a meta-stable β-type biomedical Ti−10Mo−6Zr−4Sn−3Nb (Ti-B12) alloy subjected to one-stage aging (OSA) and two-stage aging (TSA) are investigated in this work. The OSA treatment is performed at 510°C for 8 h. The TSA treatments are composed of low-temperature aging and high-temperature aging. In the first step, low-temperature aging is conducted at 325°C for 2 h. In the second step, the aging temperature is the same as that in the OSA. The result of the microstructure evolution shows that the precipitated secondary phase after aging is mainly influenced by the process of phase transition. There is a marked difference in the microstructure of the Ti-B12 alloy subjected to the OSA and TSA treatments. The needle-shaped α phases are precipitated in the parent β phase after the OSA treatment. Conversely, the short shuttle-like α phases precipitated after the TSA treatment are formed in the β matrix with the aid of the role of the isothermal ω transitional phase-assisted phase transition. The electron backscattered diffraction results indicate that the crystallographic orientation relationship of the α phases precipitated during the TSA treatment is basically analogous to those in the OSA treatment. The relatively higher tensile strength of 1,275 MPa is achieved by strengthening the effect of the short shuttle-like α precipitation with a size of 0.123 μm in length during the TSA treatment, associating with a suitable elongation of 12% at room temperature simultaneously. The fracture surfaces of the samples after the OSA and TSA treatments indicate that preventing the coarsening of the α layers in the grain boundaries is favorable for the enhancement of strength of Ti-B12 at room temperature. MTT test was carried out to evaluate the acute cytotoxicity and biocompatibility of the implanted material using L929 cells. The relative proliferation rates of cytotoxicity levels 0, 1, 2, 3, and 4 are ≥100, 80–99, 50–79, 30–49, and 0–29%, respectively. The cytotoxicity of the Ti-B12 alloy is slightly better than that of the Ti−6Al−4V alloy, which can meet the requirements of medical materials for biomedical materials.